(untitled) (Research, Society and Development, 2025)
Considering that both bacterial meningitis and Covid-19 are respiratory transmitted and that the Covid-19 pandemic led most countries to implement containment measures, such as social distancing and the use of masks, the objective of this work was to evaluate the impact of the pandemic on the epidemiological profile of bacterial meningitis in the State of São Paulo, Brazil. A survey of meningitis cases was carried out in the database of the Department of Information Technology of the Unified Health System (DATASUS), through Tabnet, to obtain the profile of the cases and to construct a historical series from 2017 to 2022. Subsequently, the ARIMA statistical model was applied to forecast the time series and compare it with real data. In the state of São Paulo, 8.346 cases of bacterial meningitis were reported during this period, of which 50.5% had unspecified etiology, 22.6% were pneumococcal meningitis, and 20.4% were meningococcal meningitis associated or not with meningococcemia. There was a significant decrease in meningitis cases in 2020 and 2021, coinciding with the most restrictive period of Covid-19 containment measures in the national and global scenario and an increase in cases at the end of 2021, when these measures became less restrictive, corroborating the impact that these measures had on the epidemiology of bacterial meningitis. Constant monitoring of bacterial meningitis cases allows not only to predict a future epidemiological scenario but also to guide the adoption of strategies to control the disease.